Pigmentation changes in brevibacteria induced by mutagenic treatment - Konícková-Radochová, M; Konícek, J; Rytír, V (Folia microbiologica, 1988)
Inducible pigmentation changes were observed in pigmented strains of Brevibacterium sp. M27 and B. flavum treated with N-methyl-N'-nitro-N-nitrosoguanidine. The highest frequency of induction was reached already at a survival of 30-40% with the maximal yield of 6-10%. As compared with the initial yellow colour, three new pigmentation types, viz. white, pink and orange, were observed. The yellow pigmented parent strains are most resistant to the lethal effects of UV radiation. By selecting pigmented mutants of all types on media containing antibiotics it was possible to obtain strains that were resistant either to tetracycline or to streptomycin. Auxotrophic pigmented mutants were also isolated. In multiple mutant strains of Brevibacterium sp. M27 a number of strainsexhibited a changed L-lysine production. In some strains the production was variable, whereasother strains did not produce L-lysine at all and stains with a limited production of other amino acids were also detected.
Keywords: kinetika; biologické pigmenty; methylnitronitrosoguanidin; Ultraviolet Rays; Species Specificity; mutace; druhová specificita; Mutation; Brevibacterium; ultrafialové záření; Methylnitronitrosoguanidine; Pigments, Biological; Kinetics